A gamification design for the classroom. Issue 1 (12th March 2018) - Hitchens, Michael; Tulloch, Rowan
Abstract : Purpose: The research described here presents an approach to gamification for the classroom. The purpose of this paper is to determine whether students would perceive the gamification activities in a positive light. Previous research has contended that students need a positive mental attitude for effective learning. The core question was to examine student attitudes to gamification, not the success of the gamification itself. Design/methodology/approach: Based on a survey of the gamification literature, and particularly drawing on the work of Groh (2012), this system is designed with three key principles in mind: relatedness, competence and autonomy. Classroom activities and associated software were designed and implemented. Almost 200 students were surveyed to determine their attitude to the gamification. The survey included both Likert-scale and qualitative responses. Findings: A majority of the students reported that they found the gamification useful and enjoyable, only a minority of students (around 15 per cent) disagreeing with such statements. However, only a minority of students perceived a relationship between the gamification activities and games. The authors conclude that well-designed gamification systems can be well-received by students and suggest that the success of gamification projects may not lie in their ability to recreate the experience of a video game, but in the strength of the relatedness, competence and autonomy of the student experience. Research limitations/implications: The research is limited by the nature of the participants, who were drawn from videogame and media units and who may be predisposed to game-like activities. Originality/value: This research demonstrates that students are able to perceive value in gamification in the classroom.